2014
DOI: 10.1515/ijnes-2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Poverty Simulation in Second Life®: Changing Nursing Student Attitudes toward Poor People

Abstract: AbstractSocial justice is a fundamental value of the nursing profession, challenging educators to instill this professional value when caring for the poor. This randomized controlled trial examined whether an interactive virtual poverty simulation created in Second Life® would improve nursing students’ empathy with and attributions for people living in poverty, compared to a self-study module. We created a multi-user virtual environment populated with famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 19 publications
5
60
1
1
Order By: Relevance
“…[12][13][14][15] Patterson and Hulton's methodology was used including the same poverty simulation, assessment tool, and data analysis strategy. 12 This study in pharmacy students showed positive improvements in attitude in 15 of 21 ATP Short Form items compared to four items in Patterson and Hulton's nursing student group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[12][13][14][15] Patterson and Hulton's methodology was used including the same poverty simulation, assessment tool, and data analysis strategy. 12 This study in pharmacy students showed positive improvements in attitude in 15 of 21 ATP Short Form items compared to four items in Patterson and Hulton's nursing student group.…”
Section: Discussionmentioning
confidence: 99%
“…12 Other nursing student studies cannot be directly compared to this study because of the variety of reporting strategies used for the ATP Short Form, which include individual items, domains, and total scores. [13][14][15] These studies used the Missouri Association for Community Action Poverty Simulation with the exception of Menzel et al, who used a virtual poverty simulation experience with a family and community resource structure similar to the Missouri Association's simulation model. [12][13][14][15] The ATP Short Form was used to measure changes in attitude toward poverty.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations